INVESTIGATION OF THE EFFECTS OF DIFFERENT ANESTHESIA COMBINATIONS ON CARDIOVASCULAR PARAMETERS IN WHITE NEW ZEALAND RABBITS - Kocaman, Yakup; Ersoz, Ugur (Slovenian Veterinary Research, 2026)
The objective of this study is to assess the morphological and physiological alterations in the heart resulting from four distinct anesthesia combinations, with midazolam, medetomidine, and dexmedetomidine applied as preanesthetics in White New Zealand rabbits. For the study, a total of 32 white New Zealand rabbits were divided into four different groups. The vertebral heart score was measured in rabbits before (T0) and at 5 (T5), 10 (T10), 30 (T30), 50 (T50) and 70 (T70) minutes during the experiment. Concurrently, measurements were taken for the electrocardiographic parameters, all at consistent time intervals. Heart frequency, respiratory rate, rectal temperature, mean arterial pressure and peripheral blood oxygen saturation were measured for a total of 60 minutes with 5 minutes intervals before and during preanesthesia. The vertebral heart score changed in all groups except the Mid+Med group. In the electrocardiographic assessment, in the Mid+Med, Deks, and Mid+Deks groups, an extension in the duration of the QRS wave and QT interval was observed, while no significant change was detected in the durations of the PR interval and T wave. Conversely, in the Me group, a distinct prolongation was observed in the duration of the P wave. Peripheral blood oxygen saturation values increased, heart frequency, mean arterial pressure and rectal temperature parameters decreased in entire groups. Following a thorough analysis of all the data in this study,it was observed that the morphological and physiological effects on the heart induced by the Mid+Med group resulted in less pronounced changes compared to the other groups. Raziskava učinkov različnih kombinacij anestezije na kardiovaskularne parametre pri belih novozelandskih kuncih Izvleček: Cilj te študije je bil ovrednotiti morfološke in fiziološke spremembe srca, nastale zaradi štirih različnih kombinacij anestezije, pri čemer so bili kot sedativi uporabljeni midazolam, medetomidin in dexmedetomidin pri belih novozelandskih kuncih. V študiji smo 32 živali razdelili v štiri različne skupine. Vrednost vertebralnega srčnega indeksa je bila merjena pri zajcih pred poskusom (T0) in po 5 (T5), 10 (T10), 30 (T30), 50 (T50) in 70 (T70) minutah med poskusom. Hkrati so bile v enakih časovnih intervalih opravljene meritve elektrokardiografskih parametrov. Srčno frekvenco, frekvenco dihanja, rektalno temperaturo, srednji arterijski tlak in nasičenost periferne krvi s kisikom smo merili skupaj 60 minut, s 5-minutnimi presledki pred in med sedacijo. Vrednost vertebralnega srčnega indeksa se je spremenila v vseh skupinah,razen v skupini Mid+Med. Pri elektrokardiografski oceni smo v skupinah Mid+Med, Dex in Mid+Dex opazili podaljšanjetrajanja vala QRS in intervala QT, medtem ko pri trajanju intervala PR in vala T nismo zaznali bistvenih sprememb. Nasprotno smo v skupini Me opazili izrazito podaljšanje trajanja vala P. Vrednosti nasičenosti periferne krvi s kisikomso se povečale, srčna frekvenca, srednji arterijski tlak in parametri rektalne temperature so se v vseh skupinah znižali.Po temeljiti analizi vseh podatkov v tej študiji je bilo ugotovljeno, da so morfološki in fiziološki učinki na srce, zaznani vskupini Mid+Med, povzročili manj izrazite spremembe v primerjavi z drugimi skupinami. Ključne besede: elektrokardiografija; radiografija; kunec; VHS